SAT0409 BIOLOGIC TREATMENT IN PSORIATIC ARTHRITIS AND AXIAL SPONDYLOPATHY REDUCES SICKNOTES ISSUED BY GPS, DESPITE DELAYS IN DIAGNOSIS: A REAL-LIFE STUDY IN WALES. (2nd June 2020) - Choy, E.; Brophy, S.; Cooksey, R.; Hanson, L.; Halliday, A.
Abstract : Background: Seronegative inflammatory arthritis including psoriatic arthritis (PsA) and axial spondyloarthropathies (AxS) are chronic inflammatory diseases associated with significant morbidities. The National Institute of Health and Clinical Excellence (NICE) has produced several pieces of guidance on disease management including the use of biologic therapies which have been shown to improve patient outcomes and quality of life. However, there are limited real-life data on patient journey from symptom onset to diagnosis and treatment including with biologics in the UK. Objectives: The purpose of this study is to examine the real-life patient journey from symptom onset to diagnosis and treatment. Methods: Data from the Secure Anonymised Information Linkage (SAIL) databank in Wales, which holds over a billion anonymised records, were used to assess the treatment of patients with PsA or AxS, aged 18 years or over with at least one READ code present for PsA or AxS in their primary care records. We examined the drug use of patients across primary, secondary care and specialist rheumatology clinics to explore the use of NSAIDs, DMARDs and biologics in the real-life setting while exploring demographics, comorbidities and surgical procedures of 1829 PsA and 908 AxS patients. Results: The AxS patients were significantly younger at diagnosis and were predominantly male. Typical delays in diagnosis of 8-9 years from symptom onset were observed. The rate of stopping or switching a biologic medication was similar for AxS and PsA patients (Table 1 ). There was a significant reduction in sicknotes issued following biologic initiation for PsA (Difference: 14.6%, 95% CI: 8.7% to 20.4%) and AxS (Difference 16.9%, 95% CI: 10.5% to 23.3%) Conclusion: Patients with PsA and AxS were treated with NSAIDs and DMARDs prior to receiving biologic medication in accordance with NICE guidelines. However, there was a long delay from symptom onset to diagnosis. Biologic treatment reduced sicknotes issued by GPs confirming the benefit of biologic treatment on work productivity observed in clinical trials. Acknowledgments: The work is funded by a Investigator-led grant from Novartis Pharmaceuticals UK Limited Disclosure of Interests: Ernest Choy Grant/research support from: Amgen, Bio-Cancer, Chugai Pharma, Ferring Pharmaceuticals, Novimmune, Pfizer, Roche, UCB, Consultant of: AbbVie, Amgen, AstraZeneca, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Chelsea Therapeutics, Chugai Pharma, Daiichi Sankyo, Eli Lilly, Ferring Pharmaceuticals, GlaxoSmithKline, Hospita, Ionis, Janssen, Jazz Pharmaceuticals, MedImmune, Merck Sharp & Dohme, Merrimack Pharmaceutical, Napp, Novartis, Novimmune, ObsEva, Pfizer, R-Pharm, Regeneron Pharmaceuticals, Inc., Roche, SynAct Pharma, Sanofi Genzyme, Tonix, UCB, Speakers bureau: Amgen, Boehringer Ingelheim, Bristol-Myers Squibb, Chugai Pharma, Eli Lilly, Hospira, Merck Sharp & Dohme, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Roche, Sanofi-Aventis, UCB, Sinead Brophy: None declared, Roxanne Cooksey: None declared, Lindsey Hanson Employee of: Lindsey Hanson is a permanent employee of Novartis Pharmaceuticals UK Limited, Anna Halliday Shareholder of: Anna Halliday owns Novartis share, Employee of: Anna Halliday is a permanent employee of Novartis Pharmaceuticals UK Ltd.